Factors affecting fertilizer use: the evidence from northern Ghana - Salin-Maradeix, Maxime (Kansas State University, 2015)
Ghana is the first Sub-Saharan African country to meet the Millennium Development Goals (MDG) of halving extreme poverty by 2015 and has made great improvement in four of the total eight MDG. Supporting by several aid programs, Ghana is right in the middle of an economic boom through agriculture with the stock exchange listing of the Ghanaian Agricultural Development Bank the 3rd of July 2015. However, many Ghanaian producers, specifically in the northern part, cannot take full advantage of this “boom” as they are dealing with poor soil quality and suboptimal levels fertilizer use. By increasing fertilizer use, producers can improve their field’s soil quality and achieve higher crop yields. The purpose of this study is to gain a better understanding of factors influencing the fertilizer use decision among smallholder producers in northern Ghana. A two-part model is estimated and takes into account number of important demographic, production and marking factors affecting producer’s decision on fertilizer adoption and amount used. Findings from this study have implication for designing private initiatives and public policies on improving smallholder producers’ agricultural productivity through the adoption of fertilizer.
Keywords: Fertilizer use; Agriculture; Decision making; Double-hurdle; Ghana; African Studies (0293); Agriculture, General (0473)